2017
DOI: 10.1155/2017/2323412
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis by Histoplasma capsulatum var. duboisii Observed at the Laboratory of Pathological Anatomy of Lomé in Togo

Abstract: Our study aimed to describe the epidemiological, clinical, and diagnostic aspects of African histoplasmosis in Togo through a descriptive and cross-sectional study on histological diagnosed African histoplasmosis in Pathology Department of Lomé from 2002 to 2016 (15 years). A total of 17 cases of African histoplasmosis were diagnosed. The sex ratio (M/F) was 1.8. The annual incidence was 1.1 cases. The mean age of the patients was 27.2 ± 0.4 years. All our patients were of social categories with a low socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 10 publications
0
25
0
9
Order By: Relevance
“…[ 3 ] The literature is not consistent about gender predilection with some authors reporting male predominance, whereas other suggested female preponderance. [ 4 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 ] The literature is not consistent about gender predilection with some authors reporting male predominance, whereas other suggested female preponderance. [ 4 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, of the 17 cases in a series from Togo, all but four cases (three in patients with AIDS and one case associated with tuberculosis) were in immunocompetent persons. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are also endemic in regions of Asia and Oceania, but the range is not clearly defined [82][83][84]. The geographical range for H. capsulatum var duboisii does not appear to extend beyond Africa, and overlaps with that of H. capsulatum var capsulatum in regions of endemicity [85,86].…”
Section: Histoplasmamentioning
confidence: 99%
“…duboisii, is rarely described in HIV infected patients in Africa (African histoplasmosis). 13,14 It was estimated that annual incidence of disseminated histoplasmosis was~100,000 cases globally in 2017. 15 The estimated incidence of histoplasmosis in 2012 was 1.48 cases per 100 people living with HIV in Latin America.…”
Section: Introductionmentioning
confidence: 99%